Acetylcholine induces intracellular Ca2+ oscillations and nitric oxide release in mouse brain endothelial cells. (September 2017) - Zuccolo, Estella; Lim, Dmitry; Kheder, Dlzar Ali; Perna, Angelica; Catarsi, Paolo; Botta, Laura; Rosti, Vittorio; Riboni, Laura; Sancini, Giulio; Tanzi, Franco; D'Angelo, Egidio; Guerra, Germano; et al.
Graphical abstract: Highlights: Acetylcholine (Ach) controls nitric oxide (NO) release from brain endothelial cells. Herein we studied the Ca 2+ toolkit underlying Ach-induced NO release from bEND5 cells. Ach-induced dose-dependent intracellular Ca 2+ oscillations in bEND5 cells. These Ca 2+ spikes were due to endogenous Ca 2+ release and store-operated Ca 2+ entry. Ach-induced Ca 2+ oscillations drove NO release from bEND5 cells. Abstract: Basal forebrain neurons increase cortical blood flow by releasing acetylcholine (Ach), which stimulates endothelial cells (ECs) to produce the vasodilating gasotransmitter, nitric oxide (NO). Surprisingly, the mechanism whereby Ach induces NO synthesis in brain microvascular ECs is unknown. An increase in intracellular Ca 2+ concentration recruits a multitude of endothelial Ca 2+ -dependent pathways, such as Ca 2+ /calmodulin endothelial NO synthase (eNOS). The present investigation sought to investigate the role of intracellular Ca 2+ signaling in Ach-induced NO production in bEND5 cells, an established model of mouse brain microvascular ECs, by conventional imaging of cells loaded with the Ca 2+ -sensitive dye, Fura-2/AM, and the NO-sensitive fluorophore, DAF-DM diacetate. Ach induced dose-dependent Ca 2+ oscillations in bEND5 cells, 300 μM being the most effective dose to generate a prolonged Ca 2+ burst. Pharmacological manipulation revealed that Ach-evoked Ca 2+ oscillations required metabotropic muscarinic receptor (mAchR) activation and were patterned by a complex interplay between repetitive ER Ca 2+ release via inositol-1, 4, 5-trisphosphate receptors (InsP3 Rs) and store-operated Ca 2+ entry (SOCE). A comprehensive real time-polymerase chain reaction analysis demonstrated the expression of the transcripts encoding for M3-mAChRs, InsP3 R1 and InsP3 R3, Stim1-2 and Orai2. Next, we found that Ach-induced NO production was hindered by L-NAME, a selective NOS inhibitor, and BAPTA, a membrane permeable intracellular Ca 2+ buffer. Moreover, Ach-elicited NO synthesis was blocked by the pharmacological abrogation of the accompanying Ca 2+ spikes. Overall, these data shed novel light on the molecular mechanisms whereby neuronally-released Ach controls neurovascular coupling in blood microvessels.